Development of Natural Science Learning Tools with Guided Inquiry Model Assisted by Real Media to Improve Students' Scientific Creativity and Science Process Skills - Aris Doyan; Susilawati Susilawati; Hardiyansyah Hardiyansyah (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to develop science learning tools with guided inquiry models assisted by real media to improve scientific creativity and science process skills of grade VIII students at SMP IT Male and SMP IT Female Mataram on light and optical equipment. The development of this tool adopts the development of Dick and Carey. The resulting products are in the form of learning tools in the form of syllabus, lesson plans, LKPD, scientific creativity instruments and science process skills. Before being used, the device was validated by four expert validators and the result was that the device developed was suitable for use in learning. To test the effectiveness of the device, scientific creativity and scientific process skills were tested. The results of the scientific creativity test obtained an average N-Gain of 0.4. This shows that the device developed is quite effective in increasing the scientific creativity of students in the two schools being the subject. The second effectiveness test is the science process skills test. The average N-Gain value obtained was 0.7, this indicates that the learning device developed with a guided inquiry model assisted by real media is very effective in improving students' science process skills.